Glycated Hemoglobin Measurement: Comparison of Three Methods Versus High Performance Liquid Chromatography - Chaila, María Zulema; Viniegra, Matías; Gagliardino, Juan José; Martínez, Alfredo; Simesen de Bielke, María Gabriela; Frusti, Mauro; Monaco, Luis; Salgado, Pablo; Buso, Carlos; Gonzalez, Claudio Daniel; Commendatore, Víctor Francisco (Journal of diabetes science and technology, 2022)
Background: HbA1c result provide information on metabolic control in diabetes mellitus (DM) and could also be used for its diagnosis. For its determination, the laboratory must be certified by the National Glycohemoglobin Standardization Program (NGSP) or the International Federation of Clinical Chemistry (IFCC) and comply with a strict quality control program. Aims: To determine the correlation and agreement between HbA1c results measured by three analytical methods (enzymatic, turbidimetric, and capillary electrophoresis) versus HPLC. Methods: Method comparison—1245 samples from equal number of subjects at 45 Association of High Complexity Laboratories (Asociación de Laboratorios de Alta Complejidad—ALAC) centers, centralizing sample processing and operator. Statistical analysis—analysis of variance (ANOVA) and nonparametric Friedman ANOVA test for related samples, means, and medians. Correlation and concordance—Pearson’s correlation and linear regression, intraclass correlation coefficient (Passing and Bablock and Bland and Altman). Results: The comparison of mean values obtained by the four methods showed statistically significant, but clinically irrelevant, differences: HbA1c by HPLC versus Electrophoresis 0.06% (0.42 mmol/mol) P = .000 (± 1.96 DS -0.070 -0.047), Enzymatic 0.087% (1 mmol/mol) P = .000 (± 1.96 DS 0.077 0.098), Turbidimetric 0.056% (0.38 mmol/mol) P = 0.000 (± 1.96 DS -0.067 -0.044). Their concordance showed intraclass correlation of single measures of 0.982 P < .001 (95% CI 0.987 - 0.9838). Conclusions: The three methods present low variability and high correlation versus the HPLC.